Independence and the promise of Peruvian life - Morán, Daniel (2020)
In the context of the celebrations of the bicentennial of independence in Latin America and the complex process of building republican legitimacy both yesterday and today, this research proposes to rethink the origins of Peruvian republicanism based on the diversity of interests of political actors in the pro-independence situation, especially between 1821-1822, taking as a source the political press. This research proposes the study of political discourses and its representations embodied in the press between the San Martín protectorate and the formation of the first Peruvian constituent congress in 1822. The objective is to document how these discursive representations were emerging in a context of plurality of political discourses in conflict motivated by the need to build a political legitimacy that would forge a new republican order.